(untitled) (Economic studies journal, 2025)
The study aimed to identify the role of accounting education in developing professional skills from the perspectives of faculty members, students, and graduates of the Accounting Department at the Faculty of Economics, University of Derna, Al-Quba Branch, and the Faculty of Economics, Omar Al-Mukhtar University. The descriptive analytical approach was followed in this study. To achieve the study’s objectives, which were to identify the role of accounting education in developing professional skills according to International Standard (3) and to test its hypotheses, a questionnaire was designed and distributed to 70 sample members, 45 of whom were returned. A total of 37 questionnaires were valid for the study. To analyze this data, SPSS statistical analysis was used. A range of statistical methods were employed, including descriptive statistics, such as frequency tables, percentages, arithmetic means, and standard deviations for the study variables. Pearson’s correlation coefficient test was also used to identify the type and degree of relationship. The field study reached several results, the most important of which are: accounting education plays a significant role, as it has a positive, statistically significant relationship in developing the intellectual skills required by the International Standards for Accounting Education (ISE) 3 among students. Accounting education plays a moderate role in developing skills (technical and functional, personal, interpersonal, and communication skills, organizational, and business management). The study recommended focusing on accounting education so that its primary goal is the quality of its outcomes, focusing on practical aspects and real-world training, so that graduates possess all professional skills